Lessons Learned From School-Based Delivery of Vision Care in Baltimore, Maryland. Issue 1 (January 2022) - Collins, Megan E.; Guo, Xinxing; Repka, Michael X.; Neitzel, Amanda J.; Friedman, David S.
Abstract : Abstract: In an effort to address health care disparities in pediatric eye care, school-based vision programs have been established. These programs, while not universally available, have been established at individual schools or across school districts in at least 20 states in the United States (US). They play a critical role for students who are not accessing eye care, especially in disadvantaged communities. In the US, school-based vision programs often provide vision screenings, eye exams, and eyeglasses directly in the school setting. The rationale for involving schools in vision care delivery is the recognition of the inter-relatedness between health and education, including how poor vision can impact learning. Vision for Baltimore is a citywide school-based vision program that provides vision care for all Baltimore City Public Schools elementary and middle school students (age range 4 to 16 years). The goal of this paper is to summarize lessons learned from our work on clinical outcomes from screenings and eye exams, the academic impact of Vision for Baltimore, and qualitative work about consent challenges and stakeholder engagement. While school-based vision programs may vary in operations, we hope the lessons learned through our work may help demonstrate the transformative impact on vision and learning, as well as the importance of addressing stakeholder needs to maximize impact and ensure program sustainability.